Is PROTAC technology really a game changer for central nervous system drug discovery?. (3rd August 2021) - Farrell, Kayla; Jarome, Timothy J.
ABSTRACT: Introduction : Central nervous system (CNS) diseases affect a large portion of the population, however, few therapeutic options are available. Furthermore, to date, clinical trials have been largely unsuccessful due to difficulty in targeting the undruggable, toxic proteins that underly many CNS disorders. PROteolysis Targeting Chimeras (PROTACs) are a rapidly emerging technology that has been proposed as a potential treatment option for various CNS diseases by hijacking the endogenous protein degradation process. Areas Covered : Herein, the authors discuss how the application of PROTACs may be beneficial in the treatment of major CNS diseases. They further discuss the main advantages and disadvantages of using PROTACs in the CNS, focusing on potential limitations such as their transient nature, localization, blood-brain barrier permeability and proteasome dysfunction. Expert opinion : It is evident that PROTACs have significant potential as a therapeutic tool for the treatment of CNS diseases and there is preliminary evidence suggesting that PROTACs could be successful in a clinical setting. Nevertheless, numerous limitations exist that must be overcome before this technology can be applied as a successful therapeutic for CNS disorders. Importantly, more in vivo studies are needed to determine the feasibility and effectiveness of using PROTACs in the brain.